Synthesis of 2- alkyl/phenyl -5-Substituted 1,3,4- Thiadiazoles - Khalid Daoud; Shaima Ismaeel; Yassir Mohamad (College of Education for Pure Sciences, 2014)
In this paper the synthesis of some 2-alkyl phenyl 5-substituted 1,3,4-thiadiazole is reported, Benzonitrile and Acetonitrile were treated with thiosemicarbazide in presence of trifluroacetic acid to give 2-alkyl/ aryl -5- amino- 1,3,4- thiadiazoles (1,2), which was treated with ethylchloroacetate in methanol to give Ethyl N-(5-alkyl/phenyl -1,3,4-thiadiazole-2- yl) glycinate (3,4), the resultant esters were converted to acid hydrazide (5,6) by their reaction with hydrazine hydrate in ethanol. Reaction of the hydrazides with benzaldehyde in ethanol gave hydrazones (7,8). Thiadiazols (1,2) were treated with ethyl chloroformate, acetyl and benzoyl chloride or benzaldehyde/ p-methoxybenzaldehyde to give substituted thiadiazoles (17,18), (9-12) and (13-16) respectively. The structure of the synthesis compounds were confirmed by IR, UV. Spectra and physical means.